Developing a Comprehensive Physical Education Curriculum in Secondary Schools: Identifying and Exploring the Key Components of Content - Yurij Vaskov (Physical Culture, Recreation and Rehabilitation)
Background and study aim. This study aims to develop and theoretically justify the content of physical education in general educational institutions, particularly in secondary schools, based on the didactic model of the subject "Physical Culture".